Enzymatic Modification of Rice Glutelin (Oryza sativa L. japonica Group) for the Development of ACE-Inhibitory Bioactive Peptides - Isnainun, Ainaya; Safitri, Lailla Nur; Khoiroh, Eka Putri Mawaddatum; Nugraha, Ari Satia; Siswoyo, Tri Agus (European Journal of Applied Sciences, 2025)
Bioactive peptides derived from plant seeds have been shown to have various biological activities, particularly in nutraceutical and pharmaceutical applications. The fact that glutelin contributes approximately 80% of total protein content indicates that rice has strong potential to generate a wide variety of bioactive peptides through protein hydrolysis, including the ability to inhibit angiotensin I-converting enzyme (ACE), making it a potential candidate for managing hypertension. In this study, rice glutelin protein was hydrolyzed using three main proteases: pepsin, trypsin, alcalase, and a combination of pepsin and trypsin for five hours. Degree of hydrolysis (DH), ABTS•+ radical scavenging and ACE-inhibitory activity of the hydrolysates were measured. The results indicated the highest DH was obtained with pepsin- and alcalase-based hydrolysates with 23%. Additionally, the ABTS•+ radical scavenging activity of the hydrolysate produced by pepsin+trypsin combination (27.64 ± 0.09 µg/mL) the ACE-inhibitory activity of the hydrolysate produced by alcalase was the highest among the other proteases (5.85 ± 0.01 µg/mL).